2017
DOI: 10.1159/000485218
|View full text |Cite
|
Sign up to set email alerts
|

SyNoPsis: Response to the Commentators

Abstract: In their commentary, Manuel Cuesta and Víctor Peralta [1] acknowledge several of the basic contributions and challenges of our SyNoPsis project. They appreciate the attempt to link clinical manifestations with the neurobiology of schizophrenia by means of a revised semiology, and the proposal to understand its essence as a disorder of interpersonal communication. The authors also recognize the aspects contributed by the important work of Carl Wernicke and Karl Leonhard [2,3]. Also, they carve out some relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The idea of the current study is inspired by the findings reported by previous researchers who attempted to link psychiatric illness with brain functions and circuits ( 33 , 34 ). For instance, the activity of the NAC, highly associated with reward processing, was found to decrease in MDD subjects ( 17 , 58 , 75 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of the current study is inspired by the findings reported by previous researchers who attempted to link psychiatric illness with brain functions and circuits ( 33 , 34 ). For instance, the activity of the NAC, highly associated with reward processing, was found to decrease in MDD subjects ( 17 , 58 , 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ROIs for the AMY, NAC, and VMPFC were the same as those used in the FC analysis while the ROIs for the DLPFC, DMPFC, and insula were specified by the 8-mm radius of a spherical ROI centered at the peak coordinate adopted from the conjunction analysis (right DLPFC [x, y, z] = [40,36,34]; left DLPFC [−36, 44, 28]; DMPFC [4,18,46]; right insula [46,18,2]; left insula [−40, 16, 4]).…”
Section: Granger Causality Analysismentioning
confidence: 99%
See 1 more Smart Citation